COVID-19 Clinical Research - Chi, Jeffrey (J Cell Signal, 2020)
INTRODUCTION: While the global COVID-19 pandemic has challenged the entire humanity and health systems, it also triggered researchers to urgently perform clinical trials to assess the safety and efficacy of many agents and modalities to combat COVID-19. As of April 22, over 650 clinical studies have been registered both in USA and internationally. Results from these studies are also coming at a brisk pace in this unprecedented emergency. AREAS COVERED: We searched the NCI website and Medline and summarize various national and international clinical trials and summarize few of the pivotal ones in this paper, including those specific to oncology population. Two hundred and eighty four studies are actively recruiting adults and children with confirmed COVID-19, including 25 are early-phase I/phase I, 72 phase II, 58 phase III, 12 phase IV, and 31 other trials. They can be categorized into four groups: drugs that combat SARS-CoV-2, immunomodulatory agents to counteract cytokine storm, convalescence plasma therapies and vaccines trials. EXPERT OPINION: It is hoped that these efforts will results in a successful treatment to COVID-19, especially in a timely fashion before the second pandemic expected in fall. It is essential to acknowledge the devotion and hard work of the clinical research team and clinical research volunteers.